Developing KPI Dashboard for The Kraft Heinz Company - Gabriela Clara (iBuss Management, 2020)
Performance Indicator has dated back to the 13th century. Since then, it had developed greatly and began to be even more important for organizations. One of the most commonly used performance indicator is known as the Key Performance Indicator (KPI). KPI, used to measure Critical Success Factor (CSF) of a company is seen to be crucial as it serves as a compass towards improvement, cost efficiency included. For The Kraft Heinz company, KPIs—displayed in a well manner through a dashboard—are needed to serve as a guideline towards improvement in cost efficiency. Thus, the purpose of this research is to build a KPI Dashboard visualization for the Kraft Heinz Company’s Distribution & Export (D&E) unit. Qualitative research through primary research and secondary research was conducted to produce the KPI Dashboard. Regarding primary research,  internal interviews with D&E team members, external interviews with business practitioner and market analyst,  and continuous rounds of feedbacks from the future user of the dashboard was gathered and analysed. Meanwhile, online journals, books, and other credible publications were used as the secondary research source. This research successfully produced a ready to use KPI Dashboard—designed using Tableau Software¬—for the D&E unit of The Kraft Heinz Company which is believed to be able to guide the organization towards a better cost efficiency.Keywords: KPI Dashboard, Key Performance Indicator, Critical Success Factor, Cost Efficiency